2019
DOI: 10.18321/ectj888
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Bitumen with Nanocarbon

Abstract: Physical and chemical indicators of bitumen quality of grade BND 70/100 with the added carbon nanopowder 2% by weight have been studied by laboratory test methods and analysis. High reaction ability of nanopowder particles and concentration of excess surface and internal energy in them have been determined, which provide the increase of low-temperature resistance, aggregate strength, and improvement of rheological properties of nanostructured bitumen. Essential structure variation has been proved: the increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The detailed information about the neat bitumen, the nanopowder and the nanocarbon bitumen and their standard and non-standard characteristics is included in our previous works [3][4][5][6].…”
Section: Materials and Methods 21 Bitumens And Nanopowdermentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed information about the neat bitumen, the nanopowder and the nanocarbon bitumen and their standard and non-standard characteristics is included in our previous works [3][4][5][6].…”
Section: Materials and Methods 21 Bitumens And Nanopowdermentioning
confidence: 99%
“…In our works [3][4][5][6] the possibility has been shown for improvement of characteristics for road bitumens by modification with a nanocarbon powder, and their standard and non-standard characteristics have been investigated. This paper is the continuation of our above works, and it shows the possibility for producing of a road asphalt concrete with the improved characteristics at the use of the bitumen with nanocarbon powder we manufactured before.…”
Section: Introductionmentioning
confidence: 99%
“…Diverting waste from landfills through their use in asphalt pavements [57] can offer various environmental, technical and economic advantages ac-cording to the concept of circular economy [58]. In particular, several studies have been reported on the use of MSW incinerator ash [59], waste tire and plastic pyrolytic chars [60], bio-oil [61] and bio-char [62][63][64], the latter both generated by the pyrolysis of biomass [65], as an aggregate substitute, modifier or additive to improve some properties of asphalt binder (bitumen). To date, no studies have been carried out on the use of char obtained from the pyrolysis of a refused derived fuel (RDF) as an additive in asphalt binder preparation.…”
Section: Introductionmentioning
confidence: 99%